Self-assessment of the health status of women diagnosed with breast cancer after surgery - Cipora, Elżbieta (Journal of Education, Health and Sport, 2017)
Introduction. Breast cancer is the most common malignancy in women in the world. Symptoms, the extent and severity of the disease process, as well as the consequences of treatment, cause unpleasant symptoms and limitations resulting from the disease. The aim of the study was to present the self-assessment of the health status of women diagnosed with breast cancer and surgically treated. Materials and methods. The study was conducted on 121 women after surgery for breast cancer in the Podkarpackie Oncological Center in Brzozów. The diagnostic survey method was used along with the original questionnaire. Results. Women who underwent a breast-saving surgery usually assessed their overall health at a good level, while respondents after breast amputation were at a sufficient level. The self-esteem of mental health of the examined women was similar. Conclusions. In the examined group there were differences in the assessment of health condition depending on the type of surgical intervention. Almost all patients diagnosed with breast cancer believed that health problems limited their functioning.